Analisis Karakteristik Fluida dan Estimasi Temperatur Reservoir di Desa Karumenga Kecamatan Langowan Utara - Ronaldo Rukait; Rolles Nixon Palilingan; Jefferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
Indonesia is a country with great geothermal potential because it is located at the meeting point of three large plates, and North Sulawesi is right in the ring of fire area, so it has large reserves of geothermal energy. The research area located in Karumenga Village, North Langowan District, Minahasa Regency, North Sulawesi Province was chosen as the research location because in that area there are surface manifestations in the form of hot springs which are estimated to come from a geothermal system. The purpose of this study was to determine the fluid characteristics and reservoir temperature estimation at the research site using geochemical methods andanalysis was carried out using the Na-K-Mg geo-indicator and the Na-K Giggenbach geothermometer. After plotting laboratory chemistry data on Giggenbach's Na-K-Mg ternary diagram, it shows that the fluid characteristics of the hot springs at the research site are partial equilibrium water where the fluid has partially changed so that it is not completely in a state of equilibrium. and based on calculations using a Na-K geothermometer, it was found that the estimated temperature of the hot spring reservoir in Karumenga Village, North Langowan District is 209.638 oC and is included in the medium enthalpy system.